Analyzing the Intertwined Crises of Hassan Rouhani’s Government (2013–2020) and their Consequences for Political Participation - Nima Shabafrooz; Ali Morshedizad; Hoseenali Nozari; Hamid Ahmadi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2023)
Introduction Both in pre- and in post-Revolution periods, Iran’s critical geopolitical and geostrategic position, as well as its revolutionary Islamic ideology, has made it a highly important player at both the regional and international levels. This sensitive and perilous position has exposed the country to various incidents and events, including economic sanctions, recreation and overt and covert support of terrorist groups, and the sale of advanced weapons to regional actors. The resulting scenarios and potential power vacuums could create a divide in political participation and society, leading to a legitimacy gap, questions of authority, and a disruption of national unity. Given the importance of the current moment and the conditions ahead, it is essential for scholarly community to analyze and provide solutions for potential crises related to political participation. Furthermore, numerous domestic and structural obstacles have emerged as significant challenges to political participation in the Islamic Republic of Iran over the past four decades, leading to a crisis and serious problems in political participation.The crisis of political participation is a clear indication of an ineffective political system. This crisis stems from a growing gap between the people and the governance system, eroding trust between political leaders and people and causing a rift between the state and the nation. This lack of trust in political leaders impedes people’s willingness to participate in the political process, resulting in political deadlocks and potentially dire consequences for society. The Purpose of ResearchThe purpose of this research was to examine the interrelated effects of multiple crises, including inefficiency, distribution, identity, influence, and legitimacy crises, on the political system, with a particular focus on the presidency of Hassan Rouhani. The research question is, what are the consequences of crises for active political participation?MethodologyThis research employed a descriptive–analytical method, utilizing a cross-sectional study of a particular time period.  FindingsBy exploring the correlations and conflicts between data, the study confirms that any political crisis signals a decrease in authority and legitimacy, ultimately resulting in a decline in active political participation and a crisis in the political system. The events of December 2017, the rise in price of gasoline and the unrest of November 2019, the Ukrainian plane crash, the crisis of inefficiency in price control, broken promises, and the distribution crisis led to a growing class divide and the decline of the urban middle class. Moreover, the gap between the language used by the governance system and the language of the people, the people’s demands and how they interacted with the political system, and the quality of their influence on politics can only be evaluated by criteria such as political participation. It is important to note that various events and occurrences, influenced by political actors and competing, parallel forces both inside and outside the government’s decision-making, have contributed to the widening scope of the crisis. However, for the purposes of this study, the term crisis refers specifically to the period of Rouhani’s administration.Discussion and ConclusionThe analysis revealed that the inefficiency crisis and distribution crisis, along with more institutionalized crises of identity and influence, erodes legitimacy at different levels, thereby reducing political participation. This study aimed to demonstrate the relationship between crises and political participation, highlighting how the inefficiency of Rouhani’s government and its inability to distribute economic and political resources fairly led to a decline in legitimacy, increased dissatisfaction, and a drop in political participation. Specifically, four major failures of the 11th and 12th governments were identified, namely, foreign policy failures, mismanagement of the Ministry of Science, failure to control the monetary and financial crisis in various markets, and failure to manage COVID–19 pandemic.